1967
DOI: 10.1172/jci105587
|View full text |Cite
|
Sign up to set email alerts
|

Absorption of Cholesterol from a Micellar Solution: Intestinal Perfusion Studies in Man*

Abstract: Summary. The absorption of cholesterol has been studied in man by perfusing the upper jejunum with a micellar solution of bile salt, 1-monoglyceride, and cholesterol-14C, with a triple lumen tube with collection sites 50 cm apart. The absorption of micellar components between the collection sites was calculated from their concentration changes relative to those of the watersoluble marker, polyethylene glycol. Control experiments were performed with cholesterol-free perfusions of saline or bile salt-monoglyceri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
76
1
2

Year Published

1972
1972
2008
2008

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 181 publications
(82 citation statements)
references
References 35 publications
(33 reference statements)
3
76
1
2
Order By: Relevance
“…In fact, the non-biliary route of fecal sterol loss may play a substantial role in maintaining sterol balance, making up a large portion of fecal neutral sterol excretion in both mice (28) and man (29). To address the quantifiable importance of this pathway in mice, Plosch and colleagues (28) treated wild type and ABCA1-deficient mice with the synthetic LXR agonist T0901317 and quantified amounts dietary cholesterol, biliary cholesterol, and fecal cholesterol to get an estimate of this nonbiliary pathway.…”
Section: Ment With Results In Acat2mentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, the non-biliary route of fecal sterol loss may play a substantial role in maintaining sterol balance, making up a large portion of fecal neutral sterol excretion in both mice (28) and man (29). To address the quantifiable importance of this pathway in mice, Plosch and colleagues (28) treated wild type and ABCA1-deficient mice with the synthetic LXR agonist T0901317 and quantified amounts dietary cholesterol, biliary cholesterol, and fecal cholesterol to get an estimate of this nonbiliary pathway.…”
Section: Ment With Results In Acat2mentioning
confidence: 99%
“…Using micellar radiolabeled cholesterol and calculating specific activity changes, the authors concluded: "cholesterol was absorbed by, and in all probability, secreted by the test segment." This study estimated that ϳ44% of total fecal sterol output in the perfused intestinal test segment originated from endogenous sources (29). Most recently, Van der Velde and colleagues (30) using a mouse intestinal perfusion system demonstrated that plasma cholesterol can traverse the small intestine in a basolateral to apical direction in a process that is dependent on bile salt and phospholipid acceptors being present in the intestinal lumen (30).…”
Section: Ment With Results In Acat2mentioning
confidence: 99%
“…Cows, for example, eat only foods that contain plant sterols, and yet their bodies contain cholesterol but not plant sterols. Investigations of such observations led to the discovery that plant sterols were excluded by the body, but could compete with bulk cholesterol for entry into the micelles formed during digestion, thus preventing dietary absorption of cholesterol [6,14,21,34,50,55,59]. Into this milieu of understanding, two key landmark observations led to a revolution in our current knowledge of how whole-body sterol balance may be achieved.…”
Section: Historicalmentioning
confidence: 99%
“…Based upon the response of patients with sitosterolemia to the drug ezetimibe, blocking NPC1L1 seems to lower plasma plant sterol levels and seems to improve symptoms and signs [52]. From studies involving mice as well as humans, the intestine can secrete cholesterol back into the lumen of the intestine [33,55]. It is possible that it may also be able to *Activation by stigmasterol in an adrenal cell line has also been demonstrated secrete noncholesterol sterols.…”
Section: Function Of Abcg5 and Abcg8mentioning
confidence: 99%
“…the low aqueous concentration of fatty acid is compensated by absorption over a longer period from a larger absorption area (39). The available experimental evidence has nonetheless led to the consideration that fatty acids and other lipids even in the presence of bile salts are absorbed from the molecular dispersed aqueous solution (60). The explanation of this apparent discrepancy may be found in the importance of the so-called unstirred layer in lipid absorption.…”
Section: Transport Of Lipids Over the Unstirred Luyermentioning
confidence: 99%